A Coronavirus Outbreak Linked to a Funeral Among a Romani Community in Central Italy - Ripabelli, Giancarlo; Sammarco, Michela Lucia; Cannizzaro, Fabio; Montanaro, Carmen; Ponzio, Guido Vincenzo; Tamburro, Manuela (Frontiers in Medicine, 2021)
Background Epidemic dynamics of COVID-19 in Molise region, central Italy, dramatically changed on the beginning of May, when high number of infections were reported among Romani people. The aims of this study were to describe the main characteristics of an outbreak occurred in the Romani community and the interventions implemented for the control. Methods A retrospective analysis of the outbreak data was performed to describe the SARS-CoV-2 transmission dynamics. Results A young Romani female was the presumed index case. The epidemiological investigation established a possible link with a funeral of a deceased member of this community. Hundred and fifty contacts within 34 family groups in two cities were traced, and 109 (72.7%) resulted to be infected. The patients with a median age of 31 years were mainly (58%) females, and the highest (20.2%) incidence occurred in the 0-to-9 years group. Twenty-six (23.8%) patients developed typical SARS-CoV-2 symptoms, 15 (57.8%) were hospitalised, and 21 (22.1%) self-reported comorbidities, mostly hypertension (28.6%) and coronary heart diseases (23.8%). The outbreak was effectively controlled enhancing the active surveillance and compulsory quarantine. Conclusions This is the first study providing insights into COVID-19 transmission dynamics among Romani population living in Italy. Findings support the role of mass assemblies for SARS-CoV-2 spread, the high communicability among close contacts and in household setting, and the impact of asymptomatic carriers that assumes even greater relevance considering Romani behaviours and family aggregation considered as a pillar in their lives. Although difficulties in interacting with Romani people related to culture drivers seriously emerged, the outbreak management was effective, and it should be considered as a valuable model for similar epidemics occurring in minority populations.